Histopathological factors versus margin size in single colorectal liver metastases: Does a 1-cm margin size matter?. (February 2022) - Fonseca, Gilton M.; de Mello, Evandro S.; Faraj, Sheila F.; Kruger, Jaime A.P.; Jeismann, Vagner B.; Coelho, Fabricio F.; Alves, Venancio A.F.; Herman, Paulo
Background and objective: The ideal margin width for surgical resection of colorectal liver metastases has been extensively studied, but not sufficiently in accordance with other pathological factors. The aim of this study was to assess for the first time the prognostic impact of margin widths according to different prognostic pathological factors in colorectal liver metastasis. Methods: We evaluated 101 patients with a single resected metastasis. Slides stained by HE were assessed for the presence of poorly differentiated clusters, peritumoral inflammatory infiltrate, tumor pseudocapsule, and tumor borders pattern. Overall survival, disease-free survival, and hepatic recurrence were evaluated. The pathologic factors prognostic impact was evaluated according to a (< or ⩾) 10-mm margin size. Results: Factors independently associated with a shorter overall survival were absence of tumor pseudocapsule ( p < 0.001) and infiltrative tumor border pattern ( p = 0.019). The absence of tumor pseudocapsule was the only factor independently associated with shorter disease-free survival ( p < 0.001). Hepatic recurrence was associated with infiltrative tumor border and absence of pseudocapsule. Margin width ⩾10 mm did not impact overall survival independently of the studied histological prognostic factors. Conclusions: In colorectal liver metastasis resection, the absence of tumor pseudocapsule was significantly associated with shorter overall survival and disease-free survival and hepatic recurrence. However, margins larger than 10 mm did not offer survival benefit when other pathologic negative prognostic factors were concomitantly analyzed, reinforcing the idea that biology, rather than margin size, is crucial for prognosis.